Delineation of a KDM2B-related neurodevelopmental disorder and its associated DNA methylation signature - Richard H. van Jaarsveld (15112408) (2023)
Purpose Pathogenic variants in genes involved in the epigenetic machinery are an emerging cause of neurodevelopment disorders (NDDs). Lysine-demethylase 2B (KDM2B) encodes an epigenetic regulator and mouse models suggest an important role during development. We set out to determine whether KDM2B variants are associated with NDD. Methods Through international collaborations, we collected data on individuals with heterozygous KDM2B variants. We applied methylation arrays on peripheral blood DNA samples to determine a KDM2B associated epigenetic signature. Results We recruited a total of 27 individuals with heterozygous variants in KDM2B. We present evidence, including a shared epigenetic signature, to support a pathogenic classification of 15 KDM2B variants and identify the CxxC domain as a mutational hotspot. Both loss-of-function and CxxC-domain missense variants present with a specific subepisignature. Moreover, the KDM2B episignature was identified in the context of a dual molecular diagnosis in multiple individuals. Our efforts resulted in a cohort of 21 individuals with heterozygous (likely) pathogenic variants. Individuals in this cohort present with developmental delay and/or intellectual disability; autism; attention deficit disorder/attention deficit hyperactivity disorder; congenital organ anomalies mainly of the heart, eyes, and urogenital system; and subtle facial dysmorphism. Conclusion Pathogenic heterozygous variants in KDM2B are associated with NDD and a specific epigenetic signature detectable in peripheral blood. Other Information Published in: Genetics in Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.gim.2022.09.006